Respuesta :
x² -10x -1 = 13
x² -10x = 14
x² -10x +25 = 39 . . . . . add (10/2)² to complete the square
(x -5)² = 39
x -5 = ±√39
x = 5 ±√39
x² -10x = 14
x² -10x +25 = 39 . . . . . add (10/2)² to complete the square
(x -5)² = 39
x -5 = ±√39
x = 5 ±√39
Answer:
Complete square: [tex](x-5)^2=39[/tex]
Solutions: [tex]x=5\pm\sqrt{39}[/tex]
Step-by-step explanation:
We have been given an equation [tex]x^2-10x-1=13[/tex]. We are asked to complete the square.
First of all, we will add 1 to both sides of our given equation.
[tex]x^2-10x-1+1=13+1[/tex]
[tex]x^2-10x=14[/tex]
Now we will add [tex](\frac{b}{2})^2[/tex] to both sides of our equation. We can see that the value of b is 10.
[tex](\frac{10}{2})^2=5^2=25[/tex]
Upon adding 25 on both sides of our equation we will get,
[tex]x^2-10x+25=14+25[/tex]
[tex]x^2-10x+25=39[/tex]
[tex](x-5)^2=39[/tex]
Taking square root of both sides we will get,
[tex](x-5)=\sqrt{39}[/tex]
[tex](x-5)=\pm\sqrt{39}[/tex]
[tex]x-5=\pm\sqrt{39}[/tex]
Adding 5 on both sides of our equation we will get.
[tex]x-5+5=5\pm\sqrt{39}[/tex]
[tex]x=5\pm\sqrt{39}[/tex]
Therefore, solutions for our given equation are [tex]x=5\pm\sqrt{39}[/tex].